Macrophage Recruitment and Polarization During Collateral Vessel Remodeling in Murine Adipose Tissue. (January 2016) - Seaman, Scott A.; Cao, Yiqi; Campbell, Chris A.; Peirce, Shayn M.
Abstract: Objective: During autologous flap transplantation for reconstructive surgeries, plastic surgeons use a surgical pre‐treatment strategy called "flap delay, " which entails ligating a feeding artery into an adipose tissue flap 10–14 days prior to transfer. It is believed that this blood flow alteration leads to vascular remodeling in the flap, resulting in better flap survival following transfer; however, the structural changes in the microvascular network are poorly understood. Here, we evaluate microvascular adaptations within adipose tissue in a murine model of flap delay. Methods and Results: We used a murine flap delay model in which we ligated an artery supplying the inguinal fat pad. Although the extent of angiogenesis appeared minimal, significant diameter expansion of pre‐existing collateral arterioles was observed. There was a 5‐fold increase in recruitment of CX3CR1 + monocytes to ligated tissue, a threefold increase in CD68 + /CD206 + macrophages in ligated tissue, a 40% increase in collateral vessel diameters supplying ligated tissue, and a 6‐fold increase in the number of proliferating cells in ligated tissue. Conclusions: Our study describes microvascular adaptations in adipose in response to altered blood flow and underscores the importance of macrophages. Our data supports the development of therapies that target macrophages in order to enhance vascular remodeling in flaps.